2020
DOI: 10.3758/s13415-020-00805-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gross motor skills, cardiovascular fitness, and visuospatial working memory-related brain activation in 8- to 10-year-old children

Abstract: Relationships between gross motor skills and cardiovascular fitness with visuospatial working memory (VSWM) in children are hypothesized to be mediated by underlying functional brain mechanisms. Because there is little experimental evidence to support this mechanism, the present study was designed to investigate the relationships of gross motor skills and cardiovascular fitness with VSWM-related brain activation in 8-to 10-year-old children. Functional magnetic resonance imaging data obtained during a VSWM-tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…For this reason, in the new era, this sport can be one of the vital ways to strengthen executive functions, including strengthening concentration and attention. The evidence shows that physical fitness increases attention and concentration and reduces the amount of distraction [15]. Koutsandreou et al [16] in their research showed that training in motor control improves children's working memory.…”
Section: Introductionmentioning
confidence: 98%
“…For this reason, in the new era, this sport can be one of the vital ways to strengthen executive functions, including strengthening concentration and attention. The evidence shows that physical fitness increases attention and concentration and reduces the amount of distraction [15]. Koutsandreou et al [16] in their research showed that training in motor control improves children's working memory.…”
Section: Introductionmentioning
confidence: 98%
“…Although previous studies have provided electrophysiological evidence to support the relationship between motor ability and VSWM (Hsieh et al, 2017 ; Tsai et al, 2012 ), these studies were unable to determine the unique contribution of motor ability to VSWM because the reported associations between motor ability and neurocognitive outcomes may be confounded by aerobic and muscular fitness, which are positively associated with working memory (Drollette et al, 2016 ; Mora‐Gonzalez et al, 2019 ; Scudder et al, 2014 ; van der Fels et al, 2020 ). Therefore, the purpose of this study was to investigate the unique association between motor ability and VSWM performance and neuroelectric indices in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Payne and Isaacs [10] stated that cognitive and motor development interact with each other and inhibit or help each other throughout life. However, research on the relationship between cognitive and motor development is limited to specific cognitive domains [11], such as working memory [12], language [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, motor and cognitive skills have long been thought of as distinct processes that develop separately and involve different brain regions [9,16]. In this regard, and rejecting the relationship with the study of different dimension effects of human development, especially cognitive and motor development, several studies have been conducted [12,17]. For example, research on the relationship between cognitive development and gross motor skills [17], as well as executive functions and motor skills [12], showed that there is a significant relationship between cognition and movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation